PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN MAKE A MATCH - suhartati suhartati (LPMP Provinsi DKI Jakarta, 2023)
The aim of this research is to improve social studies learning outcomes through the Make a Match learning model for class VI students at SD Negeri Bleber 1 for the 2022/2023 academic year. Research subjects, sixth grade students at SD Negeri Bleber 1 with addresses at Karanggede, Sumberharjo, Prambanan, Sleman, D.I. Yogyakarta. The type of research is Classroom Action Research for two cycles. Data collection instruments used observation sheets and written tests. The data analysis technique uses descriptive qualitative. The research results are seen from the percentage of learning implementation, social studies learning outcomes, and learning completion. The percentage of learning implementation by cycle I teachers was 71.4% with the criteria